2011
DOI: 10.1007/s10903-011-9458-5
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Care and Risk of Preterm Birth Among Foreign and US-Born Mothers in Michigan

Abstract: Studies among ethnic minorities suggest that prenatal care (PNC) may be less protective against preterm birth (PTB) among foreign-born relative to US-born mothers. We assessed relations between nativity, PNC inadequacy, and PTB risk over 17 years in one US state. Adjusted multivariable models were fit to assess the potential interaction between nativity and PNC inadequacy as a determinant of PTB. Additionally, we calculated predicted probabilities of PTB by PNC inadequacy, stratified by nativity. In adjusted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Assimilation and acculturation cannot be directly measured with available vital statistics data, yet these socio-cultural factors may influence the prevalence of birth defects among immigrant women, leading potentially to significantly lower or in some cases higher prevalence of specific birth defects. Previous studies have also illustrated the disparities in access to care, among foreign-born or non-US citizens compared to US-born women (Derose et al, 2007;El-Sayed and Galea, 2012;Goldfarb et al, 2017;Korinek and Smith, 2011;Massey et al, 2017). Evidence suggests that these factors should also be explored in the context of birth defects outcomes.…”
Section: | Conclusionmentioning
confidence: 99%
“…Assimilation and acculturation cannot be directly measured with available vital statistics data, yet these socio-cultural factors may influence the prevalence of birth defects among immigrant women, leading potentially to significantly lower or in some cases higher prevalence of specific birth defects. Previous studies have also illustrated the disparities in access to care, among foreign-born or non-US citizens compared to US-born women (Derose et al, 2007;El-Sayed and Galea, 2012;Goldfarb et al, 2017;Korinek and Smith, 2011;Massey et al, 2017). Evidence suggests that these factors should also be explored in the context of birth defects outcomes.…”
Section: | Conclusionmentioning
confidence: 99%
“…These results differ from the results in a study conducted in Michigan, which suggested that infants born to Arab American mothers had a reduced risk of adverse birth outcomes compared with their non-Arab American counterparts. 7,29 Differences in preterm birth and risk of having a small-for-gestational-age infant between Arab American mothers and non-Arab American mothers in Michigan and Massachusetts may be due to differences in education level, marital patterns, and maternal risk behaviors during pregnancy. 30 These differences may have also been caused by differences in methods for identifying Arab Americans in databases.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed or minimal prenatal care is associated with poor health outcomes, including premature birth, low birth weight, and neonatal and maternal morbidity . Moreover, multiple studies confirm that the most vulnerable women have lower initiation and use of prenatal care . Undocumented, low‐income immigrant women are most likely to be uninsured because many states do not offer maternity benefits to those who reside illegally in the United States .…”
Section: Introductionmentioning
confidence: 99%